The walker book of magical stories - French, Vivian (Walker Books London, 2000)
Read about Tillie McGillie's fantastical chair, the ghost of Crumbling Castle, Fred the Angel and lots more in this collection of stories by top authors such as Vivian French, Sarah Hayes and Martin Waddell